TGF-β inhibition via CRISPR promotes the long-term efficacy of CAR T cells against solid tumors - Na Tang; Chen Cheng; Xingying Zhang; Miaomiao Qiao; Na Li; Wei Mu; Xiao-Fei Wei; Weidong Han; Haoyi Wang (JCI Insight, 2020)
In recent years, chimeric antigen receptor–modified T cell (CAR T cell) therapy has proven to be a promising approach against cancer. Nonetheless, this approach still faces multiple challenges in eliminating solid tumors, one of which being the immunosuppressive tumor microenvironment (TME). Here, we demonstrated that knocking out the endogenous TGF-β receptor II (TGFBR2) in CAR T cells with CRISPR/Cas9 technology could reduce the induced Treg conversion and prevent the exhaustion of CAR T ce lls. Meanwhile, TGFBR2-edited CAR T cells had better in vivo tumor elimination efficacy, both in cell line–derived xenograft and patient-derived xenograft solid tumor models, whether administered locally or systemically. In addition, the TGFBR2-edited CAR T cells could eliminate contralaterally reinoculated xenografts in mice effectively, with an increased proportion of memory subsets within circulating CAR T cells of central memory and effector memory subsets. In conclusion, we greatly improved the in vitro and in vivo function of CAR T cells in TGF-β–rich tumor environments by knocking out endogenous TGFBR2 and propose a potentially new method to improve the efficacy of CAR T cell therapy for treating solid tumors.